UJI EFEK ANTIINFLAMASI EKSTRAK n-HEKSAN DAUN BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb) PADA MENCIT JANTAN (Mus musculus) YANG DIINDUKSI DENGAN KARAGEN - Sitti Amirah; Rahmawati Rahmawati; Safriani Rahman; Franita Achmad (Fakultas Farmasi UMI, 2014)
This research about antiinflammation effect from n-hexane extract of Beruwas Laut leaves (Scaevola taccada (Gaertn.) Roxb.) in male mice (Mus musculus) was conducted, the aim was assay the antiinflammation effect of Beruwas Laut leaves done extract based on decrease in edema volume of foot palm male mice. This research using 15 male mice that evaluated and divided into 5 groups that each group has 3 mice. In group I, diclofenac sodium as the compare administrated. In groups II, III, dan IV, n-hexane Extract of Beruwas Laut leaves in concentration of 2,5%, 5% and 7,5% administrated. In group V, 1% Na-CMC as negative control administrated. Induction carried out by injection 1% w/v carrageen 0,1 ml subcutan on the feet palm of mice. One hour later each group administered the preparation test 1 ml/30 gBW orally. The measurement of edema volume carried out prior and after administration of the tested preparation 0, 30, 60, 90, and 120 minutes. The data correlation between induction and antiinflammation effect analysed. Result indicated variety with n-hexane extract of Beruwas Laut leaves have the antiinflammation effect at concentration 7,5%. Key Word : Antiinflammation, Scaevola taccada (Gaertn.) Roxb, Mice, n-Hexane.